Is there a fertility paradox in Denmark? - Jørgen T. Lauridsen (European Regional Science Association (ERSA), 2015)
Alike most of the Western world, the Danish fertility rate declined throughout the 20th century simultaneous to economic growth. This development, which conflicts with economic intuition, has been denoted the fertility paradox, and several studies have been devoted to resolve it. The present study analyzes the geographic variation across Danish municipalities in the fertility rate during the years 1982 to 2004. Several factors commonly believed to explain the variation in the fertility rate is found to be exerted to considerable regional variation. A model linking the fertility rate to several economic determinants is established and further modified to capture geographic small-area variation. A positive correlation between regional levels of income and fertility is found, which contradicts the fertility paradox. Thus, the necessity of separating small-area and dynamic variation, aiming at obtain a proper interpretation of the link between fertility and its determinants, is demonstrated.
Keywords: C21; N3; J13; R23; 330; Spatial econometrics; Demography; Fertility; Regional population variation